Design of a 3 kW PMSM with Super Premium Efficiency - Ion, Catalin Petrea; Calin, Marius Daniel; Peter, Ioan (MDPI AG, 2023)
Extended use of permanent magnet synchronous motors (PMSMs) has brought the need to design motors that can comply with the latest requirements in terms of efficiency. This paper presents different configurations in the case of a 3 kW PMSM with two pole pairs, focusing on finding the optimal constructive solutions to ensure that it falls within the IE4 efficiency class. Six virtual prototypes were developed and simulated using the Altair FluxMotor software. A detailed comparison between the simulated versions was carried out in terms of overall efficiency, torque ripple, weight and flux density, with the focus on the nominal operating point. The results show that the virtual prototype with a relatively simple rotor design but higher stator slots number had the best results in terms of efficiency and torque ripple at the nominal operating point.